2011
DOI: 10.3727/096368910x536554
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Methods for Administering Neural Stem/Progenitor Cells to Treat Spinal Cord Injury in Mice

Abstract: To investigate potential cures for spinal cord injury (SCI), several researchers have transplanted neural stem/ progenitor cells (NS/PCs) into the injured spinal cord by different procedures, including intralesional (IL), intrathecal (IT), and intravenous (IV) injection. However, there are no reports quantifying or comparing the number of cells successfully transplanted to the lesion site by each procedure in vivo. The purpose of the present study was to determine the optimal method of cell transplantation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 69 publications
6
77
1
Order By: Relevance
“…2A) and was detectable by the IVIS bioimaging system. We also confirmed the ffLuc transduction into wt-NS/PCs, as previously reported [32]. Next, shi-NS/PCs or wt-NS/PCs were transplanted into the lesion site of NOD/SCID mice 9 days after contusive SCI.…”
Section: Grafted Shi-ns/pcs and Wt-ns/pcs Survived Within The Injuredsupporting
confidence: 57%
See 2 more Smart Citations
“…2A) and was detectable by the IVIS bioimaging system. We also confirmed the ffLuc transduction into wt-NS/PCs, as previously reported [32]. Next, shi-NS/PCs or wt-NS/PCs were transplanted into the lesion site of NOD/SCID mice 9 days after contusive SCI.…”
Section: Grafted Shi-ns/pcs and Wt-ns/pcs Survived Within The Injuredsupporting
confidence: 57%
“…This vector enabled the detection of grafted cells as strong bioluminescent ffLuc signals in live SCI mice and as fluorescent Venus signals using anti-green fluorescent protein antibody in fixed spinal-cord sections. This virus was obtained as previously reported [32]. The concentrated virus was added to the culture medium to infect primary NS/PCs derived from shiverer or wild-type mice (multiplicity of injection ¼ 1.0).…”
Section: Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] The intrathecal technique of cell injection has also been used in other animal models. [5][6][7] However, the phenotype of LP transplanted neural stem/progenitor cells (NSPCs) and bone marrow-derived mesenchymal stromal cells (BMSCs) and their spatial distribution along the intact and injured spinal cord has not been reported or quantitated. LP is a minimally invasive method of cell delivery, and stem cells may be well suited for LP transplantation because of their responsiveness to signals from the injured CNS.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the in vivo differentiation properties and safety of the diNSCs, we transplanted dissociated diNSC-derived neurospheres, which had been transduced by a lentivirus to express the Luciferase and Venus fluorescent proteins [52], into the striatum of C57/bl6j mice, as previously described [8,9]. BLI analysis [12], which detects luciferase photon signals only from living cells, showed that the cells were engrafted 28 days after their transplantation (Fig.…”
Section: Dinsc-derived Neurospheres Have Successfully Differentiated mentioning
confidence: 99%